4-year Longitudinal Study of the Assessment of Body Posture, Back Pain, Postural and Life Habits of Schoolchildren - Bruna Nichele da Rosa; Tássia Silveira Furlanetto; Matias Noll; Juliana Adami Sedrez; Emanuelle Francine Detogni Schmit; Cláudia Tarragô Candotti (Desafio Singular, 2018)
The aim of this study was to evaluate the behaviour of postural variables and the associated factors, like back pain and life habits, in schoolchildren during a period of four years. Forty-two school children underwent a postural assessment using Digital Image-Based Postural Assessment software. They also answered the self-administered questionnaire titled, "Back Pain and Body Posture Evaluation Instrument" to evaluate their back pain and life habits. We observed a significant trend of forward head, thoracic hyper kyphosis, and lumbar hyper lordosis in the entire group, as well as a trend of cervical rectification in girls. Both boys and girls presented a constant frequency in back pain, but girls presented higher prevalence along the years. We found a high prevalence of poor sitting posture in male (between 72.2-89.5%) and female (between 73.3-100%). We also found that girls had poor posture due to the way they carried their school supplies. However, occurred a decrease of time spent in front of television for male (from 87% to 10.5%) and female (from 93.3% to 0%). Significant changes occurred in analysed variables over evaluation period.